Key Performance Indicators of ewe productivity: importance of ewe body condition score and liveweight on pregnancy outcomes and lamb performance to weaning - Wright, Nerys (2021)
Body condition score (BCS) is a subjective assessment of the amount of subcutaneous fat reserves along the spinous and transverse processes of ruminants. It is an indicator of current and historical nutritional status and is considered vital for optimal ewe productivity. BCS in sheep has been documented since the early 1900’s. It can be considered to be the ratio of the amount of fat to the amount of non-fatty matter in the body of a living animal. A scale of 1 – 5 (1 being very thin and 5 being very fat) was developed during the 1960s.